Transsexuality or Homosexuality Case Report - Biçer, Ümit; Çolak, Başar; Bilgili, Murat; Dinçmen, Kriton (The Bulletin of Legal Medicine, 1996)
Transsexualism is not a sexual perversion but a condition in which an individual accepts the opposite of her or his anatomical sex during the preference of sexual identity. In order to define a man as a transsexual according to the classical approaches, he should hate everything regarding his own biological sex and the concept of being a male and anything that reminds him the male identity. To define the sexual identity of an individual as a male or female, who had undergone surgery without getting any psychological consultancy, only by the physical appearance gained by surgery will cause various medical and legal errors. In this study, two cases are presented. These two men are submitted to IV. Committee of Forensic Medicine Institute for changing their identity in the legal terms and they have been defined as "a homosexual male who had undergone surgery to be transsexual". Keywords: Gender identity, Transsexualism, Homosexualism.